Вторинна класифікація засуджених до позбавлення волі у сучасній пенітенціарній практиці України - Марчук, Альона Ігорівна; Марчук, Алена Игоревна; Marchuk, Alena (Одеса : Юрид. л-ра, 2012)
The report is a consideration of negative imprisonment results, system of allocation convicted persons into the places of imprisonment. The author has analyzed criteria which have to be taken into account during the secondary classification of mprisoned persons Also attention was paid to the positive aspects which could be brought by the effective system of classification of convicted persons.
Марчук А. І. Вторинна класифікація засуджених до позбавлення волі у сучасній пенітенціарній практиці України / А. І. Марчук // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 610-618.
Keywords: засуджений; казармена система; критерії класифікації; ресоціалізація; осужденный; казарменная система; критерии классификации; ресоциализация; on prison leave; imprisonmentit; resocialization of prisoners; reclassification